2020
DOI: 10.3390/d12090353
|View full text |Cite
|
Sign up to set email alerts
|

Pug-Headedness Anomaly in a Wild and Isolated Population of Native Mediterranean Trout Salmo trutta L., 1758 Complex (Osteichthyes: Salmonidae)

Abstract: Skeletal anomalies are commonplace among farmed fish. The pug-headedness anomaly is an osteological condition that results in the deformation of the maxilla, pre-maxilla, and infraorbital bones. Here, we report the first record of pug-headedness in an isolated population of the critically endangered native Mediterranean trout Salmo trutta L., 1758 complex from Sardinia, Italy. Fin clips were collected for the molecular analyses (D-loop, LDH-C1* locus. and 11 microsatellites). A jaw index (JI) was used to class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Exophthalmia (protrusion of the eyeballs from the skull, or 'pop eye') can be associated with the deformity (e.g. Sutton 1913;Gudger 1930;1937;Mansueti 1960;Isaacson 1965;Chew 1973;Shariff et al 1986;Palmas et al 2020), but is not always markedly obvious or present (e.g. Gudger 1930;Goodwin and Vaughn 1968;Bortone 1971Bortone , 1972Franks 1975;Pickett 1979).…”
Section: Description Of the Deformitymentioning
confidence: 99%
See 1 more Smart Citation
“…Exophthalmia (protrusion of the eyeballs from the skull, or 'pop eye') can be associated with the deformity (e.g. Sutton 1913;Gudger 1930;1937;Mansueti 1960;Isaacson 1965;Chew 1973;Shariff et al 1986;Palmas et al 2020), but is not always markedly obvious or present (e.g. Gudger 1930;Goodwin and Vaughn 1968;Bortone 1971Bortone , 1972Franks 1975;Pickett 1979).…”
Section: Description Of the Deformitymentioning
confidence: 99%
“…In rainbow trout Oncorhynchus mykiss there is evidence for vertebral deformities being partially caused by inbreeding (Aulstad and Kittelsen 1971); however, inbreeding was excluded as a factor causing vertebral deformity in Atlantic cod Gadus morhua (Gjerde et al 2005). Inbreeding was also rejected in a study of pugheaded Mediterranean trout Salmo cettii from a Sardinian stream, based on expected heterozygosity estimates (Palmas et al 2020). Hybridization can occasionally cause relatively high incidence of pugheadedness, along with other skull and jaw deformities, as seen in white bass Morone chrysops × striped bass M. saxatilis hybrids and their backcrosses in Hickey et al (1977).…”
Section: Genetic Causationmentioning
confidence: 99%
“…Conversely, Hickey (1972) observed that some specimens had the same efficiency in capturing prey, due to an enhancement in the binocular vision caused by the lifting of the eyes. In salmonids, despite the deformity, the authors found no relevant differences between normal and deformed trout, suggesting that the deformed specimen was robust and healthy (Palmas et al, 2020). Gudger and Miller (1929) mentioned two opposing scenarios: a pugheaded trout that struggled to capture the bait due to a lack of premaxilla, but a capture of an adult with a significant weight, revealing that the lack of food acquisition was not a factor to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Eels were collected between November 2019 and January 2021 from the Pramaera River (Central-Eastern Sardinia, Italy). The Pramaera River is a typical Mediterranean small watercourse characterised by biseasonal climatic features, with hot arid summers, rainy autumn/winter seasons along with extreme precipitation events, determined irregular flow, and strong seasonal hydrological fluctuations [ 72 , 73 , 74 , 75 ]. The river showed well-oxygenated waters (dissolved oxygen = 9.40 ± 12.35 mg L −1 ), good conductivity (1324.16 ± 1564.71 µS cm −1 ), and typically Mediterranean average water temperatures (16.01 ± 5.32 °C).…”
Section: Methodsmentioning
confidence: 99%